PENERAPAN ACTIVITY BASED COSTING SYSTEM UNTUK MENGHITUNG TARIF UNIT COST LAYANAN AKADEMIK BERDASARKAN SERVICE BASED DI SMK MERPATI - Kristy, Ian Panembah; ., Susilaningsih; Hamidi, Nurhasan (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objective of this research is to investigate (1) the method of calculating the amount of unit cost tariff of the academic service in five departments at SMK Merpati with the service-based approach ;and (2) the nominal amount of unit cost tariff of the academic service in the Accounting, Office Administration, Marketing, Multimedia, and Nursing departments. This research used the qualitative research method with the case study approach. The data of this research were collected through the documentation of the financial data of the school, the interview to confirm the activities, and the observation on the situation of the school. The data were then analyzed by using the theme analysis technique which connected the activi-ty domains to the cost triggers to generate the tariff of academic service per unit. The samples of this re-search consisted of the principal of the school, the vice principal for curriculum, and the treasurer of the school. The samples were gathered by using the purposive sampling technique. The results of this research are as follows (1) The Activity-based Costing method is able to be implemented at SMK Merpati by using the steps which consist of : cost identification, classification of activities, cost classification into activity pools, determination on cost triggers, cost calculation per cost trigger unit, and cost imposition on depart-ments; and (2) the nominal amount of cost tariff per unit from class X, XI, and XII for each academic ser-vice is Multimedia (Rp 294.886,62; Rp 234.693,48; Rp 239.849,16), Nursing (293.332,56; Rp 343.334,79; Rp 274.045,75), Accounting (Rp 289.245,41; Rp 238.828,48; Rp 228.260,79), Office Administration (Rp 232.945,01; Rp 294.551,25; Rp 213.771,20), Marketing (Rp 377.677,21; Rp 341.173,20; Rp 339.800.19).Keywords: Activity-based Costing method, activity, cost per unit, academic serviceABSTRAKPenelitian ini bertujuan untuk mengetahui (1) cara perhitungan besaran tarif unit cost layanan pen-didikan pada lima jurusan di SMK Merpati dengan menggunakan pendekatan service based; (2) besar nominal tarif unit cost layanan pendidikan pada lima jurusan akuntansi, administrasi perkantoran, pemasaran, multimedia, dan keperawatan. Penelitian ini menggunakan metode kualitatif dengan pendeka-tan studi kasus. Teknik sampling menggunakan teknik purposive sampling dengan sampel yang dipilih adalah kepala sekolah, waka kurikulum dan bendahara sekolah. Pengumpulan data dilakukan dengan teknik studi dokumentasi untuk data keuangan sekolah, wawancara sebagai konfirmasi aktivitas, dan ob-servasi keadaan sekolah. Analisis data menggunakan teknik analisis tema yang menghubungkan domain-domain aktivitas serta pemicu biaya untuk menghasilkan tarif layanan pendidikan per unit. Hasil penelitian adalah sebagai berikut. Pertama, ABC dapat diterapkan di SMK Merpati dengan langkah iden-tifikasi biaya, klasifikasi aktivitas, pengelompokan biaya ke dalam aktivitas, pengelompokan aktivitas ke dalam pool aktivitas, menentukan pemicu biaya, menghitung biaya per unit pemicu biaya, dan mem-bebankan biaya ke jurusan. Kedua, Nominal biaya per unit mulai dari kelas X, XI, dan XII masing-masing jurusan adalah Multimedia (Rp 294.886,62; Rp 234.693,48; Rp 239.849,16), Keperawatan (Rp 293.332,56; Rp 343.334,79; Rp 274.045,75), Akuntansi (Rp 289.245,41; Rp 238.828,48; Rp 228.260,79), Administrasi Perkantoran (Rp 232.945,01; Rp 294.551,25; Rp 213.771,20), Pemasaran (Rp 377.677,21; Rp 341.173,20; Rp 339.800.19).Kata Kunci: ABC System, Aktivitas, Biaya Per Unit, Layanan Pendidikan.